Advanced optoacoustic methods for multiscale imaging of in vivo dynamics. (9th March 2017) - Deán-Ben, X. L.; Gottschalk, S.; Mc Larney, B.; Shoham, S.; Razansky, D.
Abstract : Multiscale optoacoustic imaging – from single cells to whole organisms, from sub-millisecond biological dynamics to longitudinal studies with unprecedented image quality. Abstract : Visualization of dynamic functional and molecular events in an unperturbed in vivo environment is essential for understanding the complex biology of living organisms and of disease state and progression. To this end, optoacoustic (photoacoustic) sensing and imaging have demonstrated the exclusive capacity to maintain excellent optical contrast and high resolution in deep-tissue observations, far beyond the penetration limits of modern microscopy. Yet, the time domain is paramount for the observation and study of complex biological interactions that may be invisible in single snapshots of living systems. This review focuses on the recent advances in optoacoustic imaging assisted by smart molecular labeling and dynamic contrast enhancement approaches that enable new types of multiscale dynamic observations not attainable with other bio-imaging modalities. A wealth of investigated new research topics and clinical applications is further discussed, including imaging of large-scale brain activity patterns, volumetric visualization of moving organs and contrast agent kinetics, molecular imaging using targeted and genetically expressed labels, as well as three-dimensional handheld diagnostics of human subjects.